Faith in Feed: Exploring the Relationship Between Social Media, Religious Expression, and Mental Health for Gen Z - Defi Ela Safitri; Maisarah; Surawan (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
Generation Z is a group that grows along with the development of digital technology, so social media has become an important part of their lives. Social media is not only used as a means of communication and entertainment, but also as a space to build and display self-identity, including in the aspect of religiosity. However, the intensity of social media use often causes various psychological problems. The urge to conform to evolving trends, the desire to gain social recognition, and the habit of comparing oneself to other users have the potential to trigger stress, anxiety, and a decrease in confidence. On the other hand, the existence of religious content on social media can function as a source of inner peace, spiritual reflection, and strengthening religious values. This study uses a qualitative approach to examine in depth the influence of social media on lifestyle, mental health conditions, and the process of forming spiritual identity in Generation Z. The results of the study show that social media has an ambivalent role, namely as a factor that can cause psychological pressure as well as a medium that supports spiritual growth. An individual's ability to filter and interpret digital content is a key factor in maintaining a balance between psychological well-being and spirituality in the digital era.